Using the force and support costing system : an introductory guide and tutorial - Bigelow, J. H.; United States. Department of Defense. Office of the Secretary of Defense; National Defense Research Institute (U.S.) (Santa Monica, CA : Rand, 1999)
The Force and Support Costing (FSC) System is a set of models and databases that helps analysts project the cost implications of proposed changes in defense forces, infrastructure, and assets. The user interface and many of the models are implemented in Excel; most of the database resides on a network. The illustrated study projects effects on defense costs arising from the deactivation of an Army division. The FSC system allows the user to view the force structure in the current Army program, select the division to be cut, and specify when the deactivation will occur. The system then translates that deactivation into reductions in personnel and equipment assets, and costs out the implications. In addition to stepping through the specific procedures for the simulation, the authors show other ways the FSC System can be used to analyze the cost effects of various policy actions.
"Prepared for the Office of the Secretary of Defense by RAND's National Defense Research Institute."
Print version record.
Includes bibliographical references.
English.
eBooks on EBSCOhost
Keywords: United States; United States -- Armed Forces -- Reorganization -- Cost accounting -- Computer programs -- Handbooks, manuals, etc; United States -- Armed Forces -- Equipment -- Cost accounting -- Computer programs -- Handbooks, manuals, etc; United States -- Armed Forces -- Accounting -- Computer programs -- Handbooks, manuals, etc; États-Unis -- Forces armées -- Comptabilité -- Logiciels -- Guides, manuels, etc; TECHNOLOGY & ENGINEERING -- Military Science; HISTORY -- Military -- Other; United States; Military Administration; Military & Naval Science; Law, Politics & Government; handbooks; Handbooks and manuals; Handbooks and manuals; Guides et manuels